Hubungan Asupan Makanan (Karbohidrat, Protein dan Lemak) dengan Status Gizi Bayi dan Balita (Studi pada Taman Penitipan Anak Lusendra Kota Semarang Tahun 2016) - Virnanda Adani; Dina Rahayuning Pangestuti; M. Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Lusendra Day Care is one Day Care in Semarang City. Hour inpatient in Lusendra Day Care starting from 07.00 until 17.00. Different with other Day Care, Lusendra Day Care giving food to infants and toddlers as much as twice for infants and toddlers entrusted. Carbohydrates, proteins, and fats intake researched because energy needs carbohydrates, proteins and fats in large quantities. Energy will arise as a result of the burning of carbohydrates, proteins and fats. Purpose of this study was to analyze the relationship intake of carbohydrates, protein and fat with nutritional status of infants and toddlers in Lusendra Day Care. This study used observational research with cross-sectional approach. The sampling technique used is total sampling infants and toddlers in Lusendra Day Care, namely three babies and fourteen toddlers. Data analysis using Pearson and Spearman Rank. The results showed Day Care carbohydrate intake accounted for 63% in the adequacy of the day, protein intake accounted for 60% in the adequacy of the day and fat intake accounted for 53% in the adequacy of the day. There is a relationship between carbohydrate intake in Day Care with the nutritional status of infants and toddlers (W/H) with p-value=0.014. There is no relationship between protein intake and fat intake in Day Care with the nutritional status of infants and toddlers (W/A, H/A). There is no relationship between carbohydrate intake, protein intake and fat intake in Day Care with the nutritional status of infants and toddlers (W/A, H/A, W/H). There is no relationship between total carbohydrate intake, total protein intake and total fat intake with the nutritional status of infants and toddlers (W/A, H/A, W/H). It is advisable to hold periodic measurements of nutritional status every 1 or 2 months.